Probabilistic Finite Element Model Updating and Damage Detection of Structures by Using Bayesian Statistics - Turan, Gürsoy; Ceylan, Hasan (01. Izmir Institute of Technology, 2022)
Finite element (FE) model updating is extensively employed in many applications of various engineering branches for damage detection purposes. An FE model is expected to reflect the properties of actual structures. However, it is almost impossible for an FE model to carry the properties of the real-life structure. As a result, differences exist between analytical models and actual structures. The aim of model updating is to minimize these differences as much as possible. In model updating procedures, there are inevitable uncertainties due to inevitable measurement noise and modelling errors. Therefore, model updating and damage detection process should be performed in a probabilistic way instead of a deterministic one. To this end, Bayesian model updating methods have gained much attention in the literature to account for the uncertainties of the parameters to be updated. Among these methods, those that use the concept of system modes have gained much more attention since it enables researchers to account for modelling error uncertainties and to avoid mode matching problem. For those methods, discrepancies between system modes and measured modes are considered and system modes are updated to obtain those that best fit the measured modes. Further, system modes are connected to the FE model via eigenvalue equations. In this study, a two-stage Bayesian model updating method which utilizes the concept of system modes has been firstly reformulated to compare three different assumptions on the modelling error variance of eigenvalue equations. Results reveal that the Bayesian model updating formulations that use the system modes concept give unreasonably too small posterior uncertainties for the updated parameters. This makes the probabilistic approach questionable since getting such small uncertainties may almost be equivalent to a deterministic approach. To increase the posterior uncertainty levels to more reasonable levels, a two-stage sensitivity-based Bayesian model updating methodology is proposed in this study. The results show that the proposed method successfully improves the updating results and increases the posterior uncertainties to more realistic levels.

Sonlu elemanlar model güncelleme yöntemi, mühendisliğin çeşitli alanlarında hasar tespit çalışmaları için yaygın bir biçimde kullanılmaktadır. Bir sonlu elemanlar modelinin fiziksel yapının davranışını yansıtması beklenir. Fakat, bir modelin gerçek yapı davranışlarını bütünüyle karşılaması neredeyse imkansızdır. Fiziksel yapı ile bu yapının analitik modeli arasında her zaman bir fark vardır. Model güncellemenin amacı bu farkları mümkün olabildiğince düşürmektir. Model güncelleme yöntemlerinde, ölçüm gürültüsü ve modelleme hatalarından kaynaklı belirsizlikler de kaçınılmazdır. Bu nedenle, model güncelleme ve hasar tespiti konularında deterministik çalışmak yerine olasılıksal çalışmak daha uygundur. Bu doğrultuda, güncellenen parametrelerin belirsizliklerini de hesaba katabilmek adına Bayesyan model güncelleme teknikleri literatürde oldukça sık kullanılmaktadır. Bu teknikler arasında, sistem modlarını kullanan Bayesyan teknikleri modelleme hatasını hesaba katabilme ve mod eşleştirme sorununu önleme olanağı tanıdığı için, araştırmacıların oldukça dikkatini çekmiştir. Sistem modları, optimizasyon sürecinin bağımsız değişkenleri olup sonlu elemanlar modeline özdeğer denklemleriyle bağlanırlar. Bu çalışmada ilk olarak, sistem modları kavramını kullanan iki aşamalı bir Bayesyan model güncelleme yöntemi yeniden formüle edilmiştir. Buradaki amaç, literatürde geçen özdeğer denklemlerinin modelleme hatası varyansları üzerindeki farklı üç ayrı varsayımını kıyaslamaktır. Elde edilen sonuçlara göre, sistem modlarını kullanan Bayesyan model güncelleme tekniklerinin makul olmayan çok küçük değerlere sahip sonsal belirsizlikler verdiği gözlenmiştir. Bu sonuç, olasılıksal yaklaşımı sorgulanabilir hale getirmektedir, çünkü bu kadar küçük belirsizlik değerleri deterministik bir yaklaşıma eşdeğer sayılabilir. Bahsedilen sonsal belirsizlik seviyelerini makul düzeye çıkarabilmek adına, bu çalışmada, iki aşamalı hassasiyet tabanlı bir Bayesyan model güncelleme yöntemi önerilmiştir. Elde edilen sonuçlara göre, önerilen yöntemin güncelleme sonuçlarını başarılı bir şekilde iyileştirip sonsal belirsizlik seviyelerini daha gerçekçi düzeylere yükselttiği görülmüştür.
Yapıların Bayesyan istatistikleri ile olasılıksal sonlu elemanlar model güncellemesi ve hasar tespiti
Thesis (Doctoral)--Izmir Institute of Technology, Civil Engineering, Izmir, 2022
Includes bibliographical references (leaves. 195-204)
Text in English; Abstract: Turkish and English
Keywords: Structural damage; Bayesian model updating; Probabilistic damage detection; Finite element model updating